COVID-19 and Diabetes: Acknowledging the Bidirectional Link - Quader, Mohammad Rezaul; Khan, Mohammad Jahidur Rahman; Akram, Arifa; Islam, Md Shahidul; Mannan, Nusrat; Hossain, Md Sabir; Karim, Nurul; Juliana, Farha Matin; Bhuiyan, Amirul Huda; Deb, Paroma; Khatoon, Farhana; Mim, Farzana; et al. (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
COVID-19 and diabetes mellitus have a dynamic and bidirectional relationship. Diabetes is a risk factor for COVID-19. Diabetes mellitus is linked to hypercoagulability, inflammation, hyperglycemia, and other conditions (obesity, hypertension, cardiovascular disease, chronic kidney disease). Hyperglycemia may worsen SARS-CoV-2 infection. As a result of direct pancreatic damage caused by COVID-19, the stress response is triggered response to infection (including cytokine storm), including the use of hyperglycemic prescription medications such as corticosteroids for severe COVID-19, new-onset hyperglycemia and diabetes have been linked to the virus, as well as rapidly deteriorating blood glucose control in pre-existing diabetes. Insulin resistance and decreased b-cell secretion cause hyperglycemia. Challenges still remain in establishing the connection between COVID-19 and diabetes, whilst the pandemic progresses. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(2):99-103